Presidential Address: Contested Space: The Politics of Canadian Memory - Strong-Boag, Veronica (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1994)
AbstractNeo-conservative laments about the state of Canadian history abound. Yet the old history with its preoccupation with white male elites and its common failure to interrogate power relations and address the reality of oppression within Canadian society has rarely been equipped either to characterize the reality of the past or to address the many pressing questions of the day. The treatment of the experience of women and gender, the whole question of "race", and the place of class in Canadian society in our founding journals provides bountiful evidence of a restricted vision. It is at the very least presumptuous, and inevitably short-sighted, to believe that our profession can offer advice on Canada's on-going "national question" without first of all addressing the meaning of the oppressive relations which have produced, for example, with much else that we have ignored, our ugly inheritance of child abuse, and violence in general. When historians expand their vision, through an acknowledgement of privilege and the creation of a pluralistic community of scholars, we will be a good deal closer to coming to terms with Canadian life. This is the first step towards constructing ways of living together, whatever their exact constitutional form, that no longer require some voices to be disadvantaged while others are allowed to monopolize decision-making about what constitutes truth, citizenship and identity.